Implementing a Unique Business Identifier in Government : Guidance Note for Practitioners and Nine Country Case Studies - World Bank Group (World Bank, Washington, DC, 2016)
In an increasingly online world, governments are realizing that previous silo approaches to implementing IT systems have created barriers to the sharing of information among business regulators. As they undertake efforts to increase tax compliance, streamline business start-up, enhance data sharing, improve public service delivery, reduce administrative burdens and monitor the health of financial systems, governments are implementing unique business identifiers (UBIs) as part of their larger approach to achieving these goals and realizing the related benefits. A UBI provides the foundational information related to legal entities, enabling government and business to uniquely identify legal entities in various transactions and regulatory interactions.